The secreted protein augurin is a novel modulator of canonical Wnt signalling involved in osteoblast differentiation - Carmen Ruggiero; Nelly Durand; Marielle Jarjat; Jacques Barhanin; Elena J. Ghirardello; Michael R.G. Dack; Graham R. Williams; J.H. Duncan Bassett; Enzo Lalli (Wiley, 2022)
Abstract Background ECRG4/C2ORF40 is a tumour suppressor gene downregulated in several cancer types, which encodes the secreted protein augurin. A wide number of functions in health and disease have been assigned to augurin, but the signalling pathways it regulates are still poorly characterized. Augurin expression is strongly upregulated during in vitro differentiation of neonatal mouse osteoblasts. Methods In vitro differentiation assays of calvarial osteoblasts isolated from Ecrg4 ‐/‐ and wild‐type mice; transient transfection assays using reporters activated by Wnt signalling and other signal transduction pathways; Real‐time quantitative polymerase chain reaction for measurement of gene expression; protein expression in Chinese hamster ovary cells and Escherichia coli; in situ binding assays of proteins expressed as fusions to alkaline phosphatase with cells expressing various membrane receptors. Results Osteoblasts from Ecrg4 ‐/‐ mice have an accelerated differentiation compared to wild‐type and upregulation of Wnt markers. Augurin is a specific repressor of Wnt‐stimulated transcriptional activity, both when coexpressed together with the reporter and when added to the culture medium as a soluble protein. We confirmed the previously described binding of augurin to LOX1, a scavenger receptor, but an inhibitor of this molecule did not impair augurin repression of Wnt‐stimulated transcription specifically. Genome‐wide association studies showed an association of ECRG4 genomic variation with body height and osteoarthritis. Conclusions Our study sheds new light on the wide spectrum of functions previously ascribed to augurin in brain function, stem cell biology, inflammation/immunity and cancer. Furthermore, our discovery paves the way to further characterization of the mechanisms involved in augurin repression of Wnt signalling and the development of agonists and antagonists for this protein, which have a wide array of potential applications in the clinic.